Fuzzy Analytical Hierarchy Process for Embedded Risk Reduction in Selecting the Right Planning Decision - Abdul-Razaq, Faten F.; Al-Zubaidi, Sawsan S.; Kassam, AllaEldin H. (Al-Khwarizmi Engineering Journal, 2019)
The aim of this work is to provide an efficient selection technique as a part of planning process to guide the decision makers to decide the preferences of one supplier over another for purchasing lab instruments in education domain. Fuzzy Analytical Hierarchy Process has used as a multi-criteria decision process, as an industrial engineering tool with certain emphasis on the qualitative aspects required to the decision makers. While the concept of degree of possibility for each criterion is used to reach its relative weights, a specific methodology created to reach the final objective decision of supplier selection. A questionnaire form was developed and distributed to five universities located in Baghdad province with a total number of 100 questionnaires. The response was very adequate. Three main criteria are adopted- supplier, instruments and service performance grade. Moreover, there are sixteen sub-criteria for evaluating three potential suppliers. The final decision is reached with almost risk-free as it relates to the qualitative aspects of experts. The conclusion reached is that local supplier has a large priority weight. Microsoft Excel is used to achieve the sequential calculations for Fuzzy AHP.